The take-action guide to world class learners book 2 how to "make" product-oriented learning happen - Zhao, Yong 1965-; Tavangar, Homa Sabet; McCarren, Emily; Rshaid, Gabriel F.; Tucker, Kay (Corwin, 2016)
Your blueprint for product-oriented learning The World Class Learners series provides the most complete information available on designing twenty-first century schools poised to leapfrog into the future! These practice-oriented books expand on Dr. Yong Zhao's acclaimed World Class Learners, which presents a new framework for cultivating creative and entrepreneurial students. Now, with this second book in the follow-up three-volume set, Zhao digs much deeper, revealing how exactly to put that framework into effect. The second book in the series outlines how to . Understand entrepreneurship and project-oriented learning . Implement "making-as-learning" POL curriculum . Help students create quality entrepreneurial products . Understand ownership, copyrights, and patents Implement Zhao's new paradigm shift one phase at a time, starting with any book, depending upon your priorities. Better yet, read all three volumes for a complete blueprint to entrepreneur-minded schooling. "The ideal school should provide opportunities and resources to enable students to personalize their educational experiences instead of receiving a uniform standardized, externally prescribed, education diet." -Yong Zhao